Muslim Society's Desensitization to the Quality of Infotainment Programs on Television - Mazaya, Vyki; Rahman, Suria Hani A. (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
This study examines the desensitization of Muslim society towards the quality of infotainment on television. Although the results of the KPI survey stated that infotainment broadcasts on television were considered to be of poor quality, the reality is that they persist and are in demand. Based on the theory of value and expectation, audiences tend to consume media content when their expectations are met repeatedly. This field research uses a mixed method with a quantitative approach to test the level of desensitization. The respondents also serve as informants as data in qualitative research to determine perceptions, influencing factors, and consumption patterns of infotainment. The sample was a purposive sampling of 47 Muslims in Pekalongan with instruments adopted from the KPI survey. Data analysis used regression analysis and value and expectation theory. Desensitization in this study can be interpreted in two forms: (1) hypothesis, the audience is aware of the low quality of infotainment but still watches it, or (2) findings, the audience considers infotainment to be of good quality but rarely watches it. Compared to the national and quantitative KPI survey, this study focuses on the Muslim society in Pekalongan using a mixed-method approach. The results show that the majority of Muslims in Pekalongan still watch infotainment solely for entertainment, not because of its quality.